Children’s acquisition of word order variation: A study of subject placement in embedded clauses in Norwegian - RINGSTAD, Tina; WESTERGAARD, Marit (Journal of child language, 2024)
Norwegian embedded clauses give children two options for subject placement: preceding or following negation (S-Neg/Neg-S). In the adult language, S-Neg is the ‘default’ and highly frequent option, and Neg-S is infrequent in children’s input. However, Neg-S may be argued to be the structurally less complex. We investigate whether children are aware of the existence of both subject positions, and if they prefer the more frequent or the less complex position. Through an elicited production task with monolingual Norwegian children (N=33, age 3;1-6;1) we find that children in general overuse the Neg-S option, and we suggest that children have an inherent preference for the less complex position, due to a principle of structural economy. We also find that a group of children display U-shaped development, first using only S-Neg, then only Neg-S and finally S-Neg again, and we relate this to structure building and economy of movement.